Confessions of the Mad Wife - Hodeib-Eido, Dana (2016)
She is desperate and bitter, she believes in superstition, she is an outcast gone mad, and above all she is dead: Maryam, the narrator of Assad Fouladkar’s 2001 feature film Lamma Hikyit Maryam, is yet the only source of information available to the viewers. From her small empty room in the clinic where she has been kept and where she is receiving her psychiatric treatment, Maryam breaks her silence to tell the story of her failing marriage and her gradual breakdown, which eventually lead to her death. Using the Lebanese local dialect as its main language, Lamma Hikyit Maryam or When Maryam Spoke Out tells the story of the struggle and suffering of Maryam, a young woman who is rejected by her beloved husband and condemned by the rest of her society only because she is infertile. Fouladkar’s Lamma Hikyit Maryam renders justice to the incriminated and silenced Maryam by presenting the woman’s perspective and by exposing the dilemmas she lived through as she was trying to adapt to the harsh laws set by contemporary Arab societies.